Profile of body mass index in swimming athletes aged 7–14 years - Assidiqi, Moh. Hasbi; Ariani, Luh Putu Tuti; Yoda, I Ketut (Sriwijaya Journal of Sport, 2026)
Research Background: Swimming performance is closely associated with athletes’ anthropometric characteristics and nutritional status. Body Mass Index (BMI) is widely used as a practical indicator to assess weight–height proportionality in youth athletes; however, evidence on BMI profiles among junior swimmers at the club level remains limited. Research Objective: This study aimed to describe the BMI profile and the distribution of nutritional status categories among junior swimming athletes aged 7–14 years based on BMI-for-age standards. Method: A quantitative descriptive study with a cross-sectional design was conducted involving 40 junior swimmers (20 males and 20 females) selected through total sampling. Body weight and height were measured using standard anthropometric procedures, and BMI was calculated and classified according to BMI-for-age growth references from the Indonesian Ministry of Health. Data were analyzed descriptively and supplemented with simple comparative analysis across age groups. Results: The results showed that the mean BMI was 18.44 ± 3.68 kg/m² (range: 10.43–31.37 kg/m²). Based on BMI-for-age classification, 30.0% of athletes were severely underweight, 27.5% underweight, 35.0% normal, 5.0% overweight, and 2.5% obese. In total, 57.5% of athletes were categorized as underweight. No significant differences in BMI were observed across age groups. Conclusion: In conclusion, most junior swimmers had BMI below the normal range despite regular training. These findings emphasize the importance of regular BMI-for-age monitoring, along with appropriate nutritional interventions to support optimal growth and athletic performance.